2019
DOI: 10.1021/acs.jpcc.9b03089
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cationic Poly(ionic liquid) Architecture on the Ion Dynamics in Polymer Gel Electrolytes

Abstract: The influence of the structure of cationic poly(ionic liquid)s (PIL) on the physical properties of ternary gel electrolytes composed of PIL, Pyr 14 TFSA ionic liquid, and LiTFSA salt is investigated. The chosen PIL vary in the position of the cationic group (backbone versus side chain); spacer length and nature (alkyl or ether); and backbone rigidity. Ion gels containing PIL are analyzed in terms of thermal behavior, viscosity, ionic conductivity, ion diffusion (multinuclear Pulsed Field Gradient NMR), and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 56 publications
(130 reference statements)
0
21
0
Order By: Relevance
“…Motivated by the desire to transition polyILs toward electrochemical applications, interest has arisen in the properties of lithium salt-doped polyILs. In such a context, experiments have demonstrated that the dynamics of the free ion species (lithium ions and the counteranion of the polyIL) become faster with an increase in the concentration of lithium salt c Li . Such trends are opposite the results noted in monomeric IL systems, in which the mobility of both lithium and anions decrease with an increase in the concentration of salt.…”
Section: Introductionmentioning
confidence: 99%
“…Motivated by the desire to transition polyILs toward electrochemical applications, interest has arisen in the properties of lithium salt-doped polyILs. In such a context, experiments have demonstrated that the dynamics of the free ion species (lithium ions and the counteranion of the polyIL) become faster with an increase in the concentration of lithium salt c Li . Such trends are opposite the results noted in monomeric IL systems, in which the mobility of both lithium and anions decrease with an increase in the concentration of salt.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning an optimization of ion transport, the interplay of coexisting phases is not necessarily a drawback, as it might even be exploited in a material with a polymer-enriched phase enhancing mechanical stability, while ion transport is enhanced in IL-rich domains. This is reminiscent of ternary gels of cationic polyionic liquid (PIL) in Li-salt/IL, 55 where optimized ion transport was found for those polymeric structures, which promote a phase separation into IL-enriched and polymerenriched domains.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…However, as a result of tethering the counterion to the polymer backbone, polyILs exhibit lower ionic conductivities even relative to other salt‐doped SPEs 1,9–20 . Hence, a number of efforts have been exploring strategies such as block copolymer polyILs, 21–31 plasticizing polyILs using ILs, 32,33 salt doping polyILs 31,34–42 etc. as means to enhance the conductivity of polyIL based systems.…”
Section: Introductionmentioning
confidence: 99%